A Method for Improved Capital Measurement by Combining Accounts and Firm Investment Data - Arvid Raknerud; Dag Rønningen; Terje Skjerpen (Statistics Norway, Research Department, 2007)
We propose a new method for estimating capital stocks at the firm level by combining business accounts information and investment data. The method also produces capital estimates at the sector or industry level by summing individual firms' capital stocks and appropriately inflating this sum to account for firms with missing data. Our approach has two major advantages compared with the much used Perpetual Inventory Method (PIM). First, long investment series are not necessary. Second, sector capital estimates are automatically adjusted for changes in the capital stock because of entry and exit of firms. While capital growth rates in Norwegian manufacturing were only 1 percent on average during 1993–2004 according to national accounts figures, our method yields much higher growth rates of 5.5 percent on average.
Additional information: A revised version
Keywords: C13; C23; D24; E22; M40; 330; Capital measurement; Accounts data; Firm panel data; Net capital stocks; Depreciation